Pola Karya Konvensi pada Film Sekuel Studi Kasus Film Ada Apa Dengan Cinta? 2 - Danissa Dyah Oktaviani; Sugeng Nugroho (Jurnal Kajian Seni, 2017)
Film Ada Apa dengan Cinta? 2 is a romance drama genre fi lm that was released in 2016. This study will identify the characteristics of the genre of the fi lm Ada Apa Dengan Cinta? 2 as drama romance. Dilakuakan identifi cation process using the basic scheme of the genre. The analysis aims to look at the depth of a movie as a genre film drama romance. The theory used is a genre theory drama by Jane Stokes as the main genre and romance as a sub-genre. The results of the research will be found pieces of pictures depicting scenes drama become romance film characteristics are becoming a common convention in the fi lm Ada Apa Dengan Cinta? 2. Characteristics of the setting and location diantanya is commonly used in everyday life, using the iconography in the form of specifi c causal fashion, narrative events culinary journey, locations and adventurous vacation, the whole character is the protagonist, and the structure of the plot told a farewell and an encounter back in love triangle. As a sequel, the film has differences with its predecessor